Discovery of Palaeolithic Artefacts in Anderl, Lower Dir, Pakistan - Rahman, Lutf-ur (Ancient Pakistan, 2021)
The main objective of the present paper is to share a recent discovery of a prehistoric site with those who are interested in the Stone Age archaeology of Pakistan, as it has a rich cultural heritage. Remains of the past cultures are revealed from time to time in this region with the help of archaeological operations such as surveys, explorations and excavations. As a result, new sites of cultural significance are put on the archaeological map of the country which opens up further vistas of knowledge for researches in various fields of Pakistan archaeology. The north-western parts of Pakistan particularly the Khyber Pakhtunkhwa contributes a lot to the cultural heritage of the country. In an exploratory work, the author recently discovered stone artefacts from Anderi, Lower Dir. From their preliminary analysis the stone tools encompass the two main divisions of the Stone Age-Paleolithic and Mesolithic.